2020
DOI: 10.3390/antiox9090864
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Cardiovascular Diseases

Abstract: Reactive oxygen species (ROS) are subcellular messengers in signal transductions pathways with both beneficial and deleterious roles. ROS are generated as a by-product of mitochondrial respiration or metabolism or by specific enzymes such as superoxide dismutases, glutathione peroxidase, catalase, peroxiredoxins, and myeloperoxidases. Under physiological conditions, the low levels of ROS production are equivalent to their detoxification, playing a major role in cellular signaling and function. In pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
253
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(262 citation statements)
references
References 99 publications
2
253
0
7
Order By: Relevance
“…Numerous studies have indicated that the overproduction of reactive forms of oxygen and nitrogen is responsible for structural and functional changes in the course of myocardium inefficiency [ 29 , 87 , 88 , 89 , 90 , 91 ]. The excess of free radicals leads to the oxidation of cardiolipin, the key phospholipid of the mitochondrial membrane necessary for energy production processes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that the overproduction of reactive forms of oxygen and nitrogen is responsible for structural and functional changes in the course of myocardium inefficiency [ 29 , 87 , 88 , 89 , 90 , 91 ]. The excess of free radicals leads to the oxidation of cardiolipin, the key phospholipid of the mitochondrial membrane necessary for energy production processes.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac myocytes, most ROS are generated from the electron transport chain (ETC) [ 26 , 27 , 28 ]. Superoxide anion (O 2 •− ) is the most abundant ROS in cells [ 63 ]. The superoxide anion is formed when O 2 captures an additional electron leaking from the ETC.…”
Section: Oxidant Stress and Cardiovascular Diseasementioning
confidence: 99%
“…ROS generated by the ETC first impairs the ETC itself to further augment ROS generation [ 66 ]. Thus, the damaged ETC plays a central role in ROS generation [ 63 ] and, in that regard, may be an important pharmacological target during major operations.…”
Section: Oxidant Stress and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress, an imbalance between reactive oxygen species (ROS) production and antioxidant defense, is believed to play a key role in hypertension and cardiovascular remodeling [17,18]. In patients with primary hypertension, endogenous antioxidant enzymatic activities are reduced [19], while plasma malondialdehyde (MDA) levels are increased [20].…”
Section: Introductionmentioning
confidence: 99%